Synergistic Effect of Ciprofloxacin and Probiotics against Biofilm-Forming Pseudomonas aeruginosa - Hassan, Rasha K.; Al-Zubaidi, Saba J. Jawad (Bangladesh Journal of Infectious Diseases, 2026)
Background: the rise of biofilm- forming and antibiotic- resistant Pseudomonas aeruginosa has attempts initiatives to discover safe and natural alternative medicines, including probiotics. Objective: The current investigation sought to evaluate the antibacterial and antibiofilm properties producer derived from natural sources against clinical isolates of pathogenic Pseudomonas aeruginosa in Baghdad, Iraq. Methodology: This cross-sectional, laboratory-based in vitro study was conducted at the Department of Biology, College of Education for Pure Science, Diyala University, Iraq, from 30 October 2024 to 6 June 2026. All the patients who presented with different infectious diseases were selected as the study population. Clinical isolates of Pseudomonas aeruginosa were obtained from hospitals in Baghdad and Diyala, identified, and subsequently examined from their capacity to form biofilms and resist of antibiotics. Check the effectiveness of influence ciprofloxacin, probiotics, and their combination on biofilm formation then examination their influence on genotypic in two steps: the first step that detected biofilm genes (pelA) and quorum sensing gene (lasI). The second step was using RT-RCR technique to exam effect of synergistic of ciprofloxacin and probiotics. Results: MIC and sub-MIC levels of ciprofloxacin were (1024-512 µg/ml) while probiotics had MIC and sub-MIC levels of (100 - 75 µg/ml), so gene expression was reduced to 0.3- fold compared to the control for the pelA gene, demonstrating significant downregulation under the effectiveness of CIP alone, while gene expression was reduced to 0.2-fold compared to the control for the lasI gene under the influence of a combination of ciprofloxacin and probiotics. Conclusion: The results suggest that probiotics may enhance the efficacy of ciprofloxacin against XDR Pseudomonas aeruginosa by significantly downregulating biofilm- and quorum-sensing-related genes (pelA to 0.3-fold and lasI to 0.2-fold), indicating a potential synergistic effect in controlling this pathogen. Bangladesh Journal of Infectious Diseases, December 2025;12(2):250-259